Relationship between Financial Knowledge and Financial Satisfaction: Evidence from Investors in the Colombo Stock Exchange - Kengatharan, L. (Rajarata University of Sri Lanka, 2021)
Financial satisfaction is the result of a certain form of behaviour involving how people manage their money to meet their financial needs. Financial demand is said to be effective if it can fulfil the short and long term consumption needs of individuals without any flaws. This research aims to examine the relationship between financial knowledge and financial satisfaction. The investors in the Colombo Stock Exchange who live in the Jaffna district were considered for this study, and convenient sampling was used to select the participants. Financial knowledge was considered as the independent variable, while financial satisfaction was considered as the dependent variable. Statements have been used in the questionnaire to measure financial knowledge and financial satisfaction using 5 points Likert Scale. The primary data was collected via a questionnaire from 186 individual investors covering the period from June to July 2020. The Cronbach's Alpha values were greater than 0.7, indicating that the variables were reliable. The results of regression analysis revealed that there is a significant impact of financial knowledge on financial satisfaction. Therefore, it was concluded that there is a significant relationship between financial knowledge and financial satisfaction. To generalize the results, future researchers should include more variables that could affect financial satisfaction, as well as include more respondents.
Keywords: Financial knowledge; Financial satisfaction; Individual investors